Lingual Papillae in Hamdani Sheep During Foetal Periods: Gross, Scanning Electron Microscopy, Histochemical and Immunohistochemical Analysis - Barış Can Güzel; İhsan Işbilir; Senem Esin Yavaş; Fatma Işbilir (Veterinary Medicine and Science)
ABSTRACT This study aimed to investigate the developmental, macroscopic, microscopic and immunohistochemical characteristics of tongue tissues in sheep foetuses collected at three gestational periods. The study was carried out with foetuses collected from pregnant ewes slaughtered in private slaughterhouses. For this purpose, a total of 15 foetuses, 5 each from the first trimester (38–48 days), second trimester (56–73 days) and third trimester (105–118 days), were used. Foetal tongues were carefully dissected and removed from the oral cavity. First, their macroscopic properties were examined using a stereomicroscope. Scanning electron microscopy was used for microscopic morphological evaluations, and the tongues were examined under a light microscope using Haematoxylin Eosin and Masson Trichrome methods. The expression and localization of cytokeratins (CK)‐5, E‐cadherin, EphB2 and EphB3 proteins in the tongue epithelium were determined by immunohistochemical analysis. According to the results of light and electron microscopy, it was determined that the tongue tissue began to develop in the first trimester, and lingual papillae could be seen as primitive primordia. Although the tongue continued to grow in the second trimester, primitive taste buds and papilla structures were detected. In the last trimester, lingual papillae were observed to become more prominent. In addition to taste buds, serous glands in the papillae were also detected. It was determined that both taste and mechanical papillae formed simultaneously during the development of lingual papillae, and the papillae were located at the apex, body and root without a chronological order. Furthermore, epithelial markers such as CK‐5 and E‐cadherin as well as EphB2 and EphB3 receptor expressions were detected in the epithelium covering the papillae in all three trimesters. In addition to contributing to the morphological literature, our results may provide information for future studies aimed at elucidating the normal development of the tongue and other epithelial tissues in sheep.